Information from Bird Nests Monitored on the Colville River Delta, Alaska, 2011-2018 ... - Daniel R Ruthrauff (U.S. Geological Survey, 2020)
This dataset contains nesting information for birds breeding at a site on the Colville River, Alaska, 2011-2018. Nests were located during area searches conducted by biologists, and standardized information on each nest was collected following protocols of the Arctic Shorebird Demographic Network (Brown et al. 2014). ...